Implementation of routine interferon-gamma release assay testing in a South London HIV cohort. (March 2020) - Sandhu, Preeti; Taylor, Chris; Miller, Robert F; Post, Frank A
Human immunodeficiency virus (HIV) infection is a major risk factor for the development of tuberculosis (TB). Although guidelines recommend that people with HIV from high TB incidence countries and those with risk factors are screened for latent TB infection (LTBI) using interferon-gamma release assays (IGRAs), this has not been widely implemented in the UK. We introduced universal LTBI screening using IGRAs at nurse-led induction clinics for patients newly presenting, transferring or re-presenting for HIV care and conducted a prospective audit from 1 January 2018 to 30 June 2019 to identify operational challenges as well as opportunities for TB prevention. Of the 223 patients, 17 had active or previously treated TB. Of the remaining 206 individuals who were eligible for IGRA testing, 78 (38%) were not tested due to logistical issues, failure to request the test or no induction visit taking place. Of the 128 (62%) individuals who were tested for LTBI, 3 (2.3%) had a positive IGRA, 4 (3.1%) an indeterminate result and 121 (94.5%) a negative result. All seven with positive/indeterminate tests were of African/Caribbean background, had CD4 cell counts >200 cells/mm 3 and HIV RNA <400 copies/ml. Our audit suggests that universal LTBI screening was logistically challenging and provided few opportunities for TB prevention.